PEMBELAJARAN MENYIMAK (MIRENGANG) “SATUA BALI” BERBANTUAN MEDIA AUDIO VISUAL BAGI SISWA TUNAGRAHITA - Luh Sukertiasih; I Ketut Ngurah Ardiawan (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
This study aims to describe (1) listening learning (mirengang) "Satua Bali" assisted by audio visual media for mentally disabled students, and (2) implementation of listening learning (mirengang) "Satua Bali" assisted by audio visual media for mentally disabled students. This study uses a descriptive qualitative research design. The subject in this study was a teacher who taught retarded students in IIC class SDLB Negeri 1 Buleleng and the object was listening to learning (mirengang) "Satua Bali" assisted by audio-visual media. The data collection method uses the method of documentation, observation and interviews. Analysis of the data used is descriptive qualitative analysis. The results showed that (1) the teacher was able to design listening media (mirengang) "Satua Bali" assisted with audio-visual media through YouTube videos and the teacher told stories with the help of pictures. (2) the implementation of listening to (mirengang) "Satua Bali" assisted by audio visual media is effectively carried out by the teacher. This is evident from the conducive learning situation, and there is an increased interest in student learning. Keywords: audio visual, listening (mirengang), mental retardation